Palynology and paleoenvironmental significance of the Tunal Formation (Danian) at its type locality, El Chorro creek (Salta, Argentina) (Ameghiniana, 2013)
Abstract. The palynologic investigation of samples from the Tunal Formation at El Chorro creek (Salta, Argentina) resulted in the recovery of terrestrial assemblages of pollen and spores associated with freshwater algae (Pediastrum spp. and Scenedesmus sp.). Of the 43 species of sporomorphs identified for the Tunal Formation so far, 28 species are cited here for the first time. The spores and pollen indicate a Danian age at the type locality. Sedimentary proxidata including abundant evaporites suggest intervals of at least seasonal arid environmental conditions. In contrast, the palynologic assemblages recovered from the organic rich dark shales indicate the presence of swampy areas and forests surrounding them. The dominance of Verrustephanoporites simplex Leidelmeyer (corresponding to the modern Phyllostylon, Ulmaceae) indicates abundant seasonal rainfalls, warm humid conditions and subtropical climate. Resumen. PALINOLOGÍA E IMPORTANCIA PALEOAMBIENTAL DE LA FORMACIÓN TUNAL (DANIANO) EN SU LOCALIDAD TIPO, QUEBRADA EL CHORRO (SALTA, ARGENTINA).La investigación palinológica de muestras extraídas de la Formación Tunal en la quebrada El Chorro (Salta, Argentina) resultó en la recuperación de una asociación de polen y esporas, juntamente con algas de agua dulce (Pediastrum spp. y Scenedesmus sp.). De las 43 especies de esporomorfos identificadas hasta el momento para la Formación Tunal, 28 se citan aquí por primera vez. Las esporas y polen indican edad Daniana en la localidad tipo. Los proxidata sedimentarios incluyendo abundantes evaporitas, sugieren intervalos al menos estacionales de condiciones ambientales áridas. Por otro lado, las asociaciones palinológicas recuperadas de las pelitas oscuras ricas en materia orgánica indican la presencia de áreas anegadas y selvas en sus alrededores. En las últimas, el predominio de Verrustephanoporites simplex Leidelmeyer (que se corresponde con el actual Phyllostylon, Ulmaceae) indica abundantes lluvias estacionales, condiciones cálido-húmedas y clima subtropical.